Prospect of Eco-Tourism in Upper Humla (A Case Study of Namkha Rural Municipality) - D.C., Daman Dhoj (Academia Research Journal, 2024)
Tourism, as the world's largest and fastest-growing industry, holds significant potential for economic development and cultural exchange. Nepal, endowed with natural beauty and cultural heritage, has positioned itself as a prime destination for global travelers seeking tranquility and environmental conservation. In this context, eco-tourism emerges as a sustainable alternative, minimizing environmental impacts while promoting conservation and community development. Upper Humla, a region rich in biodiversity and cultural diversity, stands out as a promising area for eco-tourism development within Nepal. This study explores the prospects of eco-tourism in Upper Humla, focusing on its natural resources, cultural attractions, and the potential economic benefits for local communities. Using a descriptive and exploratory research design, data was gathered through surveys, interviews, and observations to assess tourist preferences, eco-tourism resources, and local perceptions. The findings highlight the unique opportunities and challenges in harnessing Upper Humla's tourism potential, aiming to contribute to sustainable tourism practices and regional development strategies in Nepal.